Improving the field production environment for soybeans - Lam-Sánchez, A. [UNESP] (Wiley, 1981)
During the past 10 years, soybeans have reached a prominent position among crops in the world. A substantial contribution to world production has been achieved by tropical countries, due to favorable conditions for high yields. Two limitations keep commercial yields below those obtained in experimental results (above 3,000 kg/ha): one is the lack of local adapted varieties and the other is an adequate field production environment. Solutions must be obtained by local research data. Seedbed preparation is one of the most important production steps, since the other production practices are dependent on it. Conventional methods and minimum tillage, when soybeans follow another crop, are being used, with the problem of soil compaction and losses by erosion. Looking for superior strains of Rhizobium is crucial because nitrogen can be supplied by a proper symbiosis. The addition of limestone to the soil is a common practice used to raise the pH to proper levels. The use of fertilizers should be guided by local research findings. Chemical control of weeds, pests and diseases is needed to prevent yield losses, but possible effects on the environment should be considered. © 1981 American Oil Chemists' Society.